Development of a multi-objective stepwise data envelopment analysis method based on common set of weights to evaluate the agility of decision-making units: a case study. (22nd August 2022) - Darijani, Moosa; Amiri, Maghsoud; Taghavifard, Mohammad Taghi; Hanafizadeh, Payam
In most data envelopment analysis (DEA) models, the internal structure of production units is ignored during the evaluation process. To solve this problem, a stepwise DEA model has been considered by the researchers. Another weakness of classical DEA models is that the weights of inputs and outputs are being changed each time the model is run. In such case, the common set of weight method is one of the popular ranking methods which can well identify efficient and inefficient units based on the same criteria. In the present study, using the related studies in the literature, a conceptual model considering agility dimensions was constructed, in which the main dimensions include drivers, enablers, capabilities and agility results. Then, a model for calculating the performance weights is presented. The model was applied to evaluate the agility performance of 11 technical and vocational training centres in Kerman Province. At the end, the obtained results were analysed and suggestions were made for interested researchers for future studies in this field.